Expert System for Selection of Academic Programme (ESSAP) - Wannoraini, Abdul Latif (2005)
Expert system is one of the important application oriented branches of Artificial Intelligence. At the beginning of development expert systems in education, the area selected is application to selection of academic programme. ESSAP is a web-based system that are different from conventional computer programs as they can solve problems by mimicking human reasoning processes, relying on logic, belief, rules of thumb, opinion and experience. This system provides academic programme for School of Information Sciences & Engineering (SISE) at University College of Technology & Management Malaysia (KUTPM). The web programming languages of system implementation are PHP, JavaScript and CSS. The knowledge base was created using MySQL database server. ESSAP system provides advisory and recommendation for academic programme for the students based on their qualification and interests. The system would determine type of student's personalities from their interest, using Holland J. Theory.